Pengaruh Perubahan Kurikulum 2013 ke Kurikulum 2006 (KTSP) Terhadap Proses Pembelajaran (Studi Kasus di SMP Negeri 1 Kepung) - nur huda (LPPM IAI Hasanuddin Pare-Kediri, 2015)
In the country of Indonesia, the government has issued various policies to improve the quality of education. Noted there are several times changes (refinement) curriculum ever applied in Indonesia. The last three curriculum implemented since the regional autonomy policy are Curriculum 2004 (KBK), Curriculum 2006 (KTSP), and Curriculum 2013. The focus of the study is the impact of curriculum change on the ongoing learning process. For the object of research, the authors chose to study SMPN 1 Kepung. Influence / positive impact: provide convenience to the teacher on the aspect of the assessment, 72% of students value of learning rise. The negative effect: the hard work of the teacher working on the app is futile, the student has 2 reporting books in one lesson of year, and the 2013 curriculum books that are piled up about one meter become unused.